Facial nerve paralysis following endodontic treatment of lower first molar. Issue 3 (May 2016) - Demetoglu, Umut; Ozkan, Gokhan; Simsek, Hasan Onur
Abstract: Facial nerve palsy is a common cranial nerve disorder that affects facial mimic movements. Mostly, it is caused by idiopathic conditions, such as trauma or tumors located in parotid gland. Facial nerve palsy from dental infection is rare and only a few cases were reported up to date. The authors highlight the etiology of facial nerve paralysis and the effects of regional odontogenic infections on nerve damage. This article describes a case report of a 21-year-old female patient who represents unilateral facial nerve paralysis after endodontic therapy. The paralysis occurred in 2 days after endodontic treatment with a swelling at perimandibular and retromandibular regions. Her right mandibular first molar was extracted under antibiotic therapy and the swelling was disappeared. In her first follow-up session, she could move her lip slightly and facial nerve palsy decreased quite a lot. Physicians should be aware the effects of dental infections to facial nerve and should refer patients to a specialist for a proper management.